What's Public About Crime?. (24th May 2016) - Edwards, James; Simester, Andrew
Abstract: It is often claimed that the fact that some wrongs are public is a fact that is important to our thinking about permissible criminalisation. We argue that it is not. Some say: what gives us reason to criminalise wrongs—when we have such a reason—is the fact that those wrongs are public. Others say: the fact that a wrong is public is a necessary condition of there being reason to criminalise that wrong, or of its permissible criminalisation. What we should make of these statements depends on what is meant by a public wrong. If the claim that a wrong is public is simply the conclusion of a sound argument that there is reason to criminalise the wrong, or that the wrong is permissibly criminalised, the above statements are true, but trivially so. If the claim that a wrong is public is a premise in an argument that there is reason to criminalise the wrong, or that the wrong is permissibly criminalised, the above statements, we argue, are false. We conclude that it would be better, when we think about permissible criminalisation, to do without the idea of a public wrong.